2012
DOI: 10.1137/100808824
|View full text |Cite
|
Sign up to set email alerts
|

Induced Matchings in Subcubic Planar Graphs

Abstract: Abstract. We present a linear-time algorithm that, given a planar graph with m edges and maximum degree 3, finds an induced matching of size at least m/9. This is best possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Theorem 1 implies the following corollary. This corollary extends a result of Kang, Mnich and Müller [16] to loopless multigraphs. Joos, Rautenbach and Sasse [15] later showed that the above lower bound holds for all subcubic graphs, thus proving a conjecture of Henning and Rautenbach [10].…”
Section: 6supporting
confidence: 85%
“…Theorem 1 implies the following corollary. This corollary extends a result of Kang, Mnich and Müller [16] to loopless multigraphs. Joos, Rautenbach and Sasse [15] later showed that the above lower bound holds for all subcubic graphs, thus proving a conjecture of Henning and Rautenbach [10].…”
Section: 6supporting
confidence: 85%
“…Theorem 2 actually implies the main result of Kang, Mnich, and Müller, Theorem 1 in [10], stating that every subcubic planar graph G of size m(G) has an induced matching of size at least m(G)/9, which can be determined in linear time. In fact, since K + 3,3 is not planar, every subcubic planar graph G satisfies n + 3,3 (G) = 0.…”
Section: Introductionmentioning
confidence: 54%
“…Our proof of Theorem 2 is constructive and leads to a linear time algorithm to determine an induced matching of the guaranteed size as we will explain below. While the proof in [10] is extremely involved, our proof of Theorem 2 is quite simple. One reason for this simplicity is probably the fact that we express the lower bound on the strong matching number in terms of the order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For subcubic planar graphs, Kang, Mnich and Müller [9] showed that ν s (G) ≥ m(G) 9 . This was improved by Rautenbach et al [7]…”
Section: Introductionmentioning
confidence: 99%